2018
DOI: 10.1111/jgh.14148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraduodenal acetic acid infusion on pancreatic duct cannulation during endoscopic retrograde cholangiopancreatography: A double‐blind, randomized controlled trial

Abstract: Intraduodenal acetic acid infusion can significantly decrease difficult pancreatic cannulation rate, facilitate pancreatic duct cannulation, and reduce radiation exposure (ClinicalTrials.gov number, NCT02800772).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…The limitations of secretin, such as its high price and limited availability, makes its use complicated in clinics[97]. Alternatively, intraduodenal acid infusion (ACI) was used in clinical trials, since it can physiologically stimulate secretin release in the body[98,99].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of secretin, such as its high price and limited availability, makes its use complicated in clinics[97]. Alternatively, intraduodenal acid infusion (ACI) was used in clinical trials, since it can physiologically stimulate secretin release in the body[98,99].…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, intraduodenal acid infusion (ACI) was used in clinical trials, since it can physiologically stimulate secretin release in the body[98,99]. Fang et al[97] conducted a single center, double-blind RCT between 2016 and 2017 in China to investigate the impact of ACI on pancreatic duct cannulation during ERCP. Consecutive patients were randomized into two groups (105 in each group) and received 50 mL ACI infusion or 50 mL saline.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether SCT is an oncogene or a tumor suppressor is still controversial. A number of studies hold the idea that it is an oncogene, as high expression was observed in breast cancer [44], whereas other studies indicated the downregulation of the gene in colorectal cancer [45] and prostate cancer [46]. SCT acts as a gene with double-edge sword activities, which possesses both oncogenic and tumorsuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, a admistração do análogo de secretina, que é um hormônio peptídico gastrointestinal o qual promove a liberação pancreática de bicarbonato, pode contribuir para a canulação. As limitações desse hormônio tornam o seu uso inviável pelos hospitais, visto que possui alto preço, bem como pouca disponibilidade (FUNG et al, 2021) A infusão intraductal de ácido acético, também, pode facilitar a canulação. É uma abordagem fisiológica que estimula a liberação de secretina endógena.…”
Section: Farmacoprevençãounclassified
“…É uma abordagem fisiológica que estimula a liberação de secretina endógena. Em um ensaio clínico randomizado e duplo-cego com 210 pacientes observou que esse ácido pode diminuir a taxa de canulação do ducto biliar comum (FANG et al, 2018) Alguns outros medicamentos foram estudados para tentar reduzir o bloqueio temporal do fluxo de eliminação do suco pancreático, causado pelo edema papilar e/ou espasmo do esfíncter de Oddi. Dentre eles, o gliceriltrinitrato e o nitrato de glicerila que auxiliam no relaxamento do esfíncter de Oddi e facilita a canulação primária.…”
Section: Farmacoprevençãounclassified